(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Immediately after World War II, the world faced a tremendous challenge, which centered on the answer to the following question: How do we obtain justice after all the criminal practices that occurred prior to and during the Second World War on an unimaginable scale? With the emergence of specific vocabulary to describe the atrocities that would later be termed genocide crimes, lawmen wanted to develop legislation to deal with these unprecedented crimes, in this regard, the Allied countries and European governments organized a series of war crimes trials, and these trials were not free of politicization. It is imperative to propose the achievement of an objective international criminal justice that is far from politicization. The beginning was with the 1948 Convention on the Prevention and Punishment of Genocide, followed by various international efforts until the 1998 Rome Statute. These conventions listed acts that constitute genocidal crimes and some of these acts contained in these conventions are punishable by the Syrian legislator as crimes of murder and victimization. . . . Etc., so it was necessary to make a comparison between these agreements and the Syrian legislation.